2016
DOI: 10.1038/srep25677
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine: a conformational marker that regulates the substrate specificity of human demethylases FTO and ALKBH5

Abstract: N6-Methyladenosine (m6A) is currently one of the most intensively studied post-transcriptional modifications in RNA. Due to its critical role in epigenetics and physiological links to several human diseases, it is also of tremendous biological and medical interest. The m6A mark is dynamically reversed by human demethylases FTO and ALKBH5, however the mechanism by which these enzymes selectively recognise their target transcripts remains unclear. Here, we report combined biophysical and biochemical studies on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 58 publications
(112 reference statements)
4
114
0
1
Order By: Relevance
“…The original studies on FTO-mediated m 6 A demethylation [25], as well as follow-up studies [46], showed that FTO efficiently demethylates m 6 A irrespective of sequence context. The original studies on FTO-mediated m 6 A demethylation [25], as well as follow-up studies [46], showed that FTO efficiently demethylates m 6 A irrespective of sequence context.…”
Section: Inconsistencies With M 6 a As The Substrate Of Ftomentioning
confidence: 99%
“…The original studies on FTO-mediated m 6 A demethylation [25], as well as follow-up studies [46], showed that FTO efficiently demethylates m 6 A irrespective of sequence context. The original studies on FTO-mediated m 6 A demethylation [25], as well as follow-up studies [46], showed that FTO efficiently demethylates m 6 A irrespective of sequence context.…”
Section: Inconsistencies With M 6 a As The Substrate Of Ftomentioning
confidence: 99%
“…The m6A demethylases: focus on FTO In mammals, two m6A demethylating enzymes have been identified to date, namely the fat mass and obesity-associated (FTO) protein (Jia et al 2011) and Alkbh5 (Zheng et al 2012). Both belong to the AlkB family of the Fe(II)/aketoglutarate-dependent dioxygenase superfamily and possess a similar catalytic core, although they have different substrate preferences (Aik et al 2014;Zou et al 2016) and are differentially expressed in different mammalian organs (Gerken et al 2007;Zheng et al 2012). ALKBH5 is highly expressed in testis and is essential for spermatogenesis (Zheng et al 2012).…”
Section: The M6a-machineriesmentioning
confidence: 99%
“…This not only indicates a compensatory mechanism driven by Alkbh5, but also raises the question of whether FTO and Alkbh5 have different substrate specificity. A modeling study of m6A containing RNAs suggests that the conformational change induced by m6A could be a critical factor for FTO or ALKBH5 recruitment (Zou et al 2016).…”
Section: The M6a-machineriesmentioning
confidence: 99%
“…1517 Alkbh3 hydroxylates methyl lesions in single-stranded (ss) DNA as well as m 1 A in mRNA, thereby expanding the substrate range to RNA. 18 Alkbh5 and FTO also act on RNA, 1922 but these enzymes demethylate 6-methyl adenine (m 6 A) in this substrate in vitro , affecting mRNA stability. 1 In vivo , Alkbh5 plays a role in fertility while FTO is important for controlling body weight in mice and humans.…”
mentioning
confidence: 99%